The Glass Beads of the Prehistoric and Roman Periods in Britain and Ireland - Guido, Margaret (Reports of the Research Committee of the Society of Antiquaries of London, 1978)
This book discusses the glass beads of Britain and Ireland. It provides a classification and chronology of beads, mainly of the Iron Age and Roman periods, but extending back into the Bronze Age. Supported by colour plates and line illustrations, it describes a series of detailed Schedules, arranged by Classes on a geographical basis and is supported by distribution maps.